2014
DOI: 10.1111/jtm.12160
|View full text |Cite
|
Sign up to set email alerts
|

Serious Altitude Illness in Travelers Who Visited a Pre‐Travel Clinic

Abstract: Serious altitude illness was a very frequent problem in travelers who visited pre-travel clinics. Young age, dark urine, travel in South America or Africa, and lack of acclimatization nights at moderate altitude were independent predictors. Furthermore, we found that seriously ill travelers seldom followed the advice to descend and to visit a physician.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
1
8
0
1
Order By: Relevance
“…There is some data to suggest that changes in HRV may be linked or even predictive of AMS though this still remains controversial (Lanfranchi et al, 2005;Chen et al, 2008;Koehle et al, 2010;Karinen et al, 2012;Wille et al, 2012;Song et al, 2013). This has important clinical implications as travel to HA has significantly increased in the last 10 years and AMS affects ≥35% of persons traveling to altitudes ≥3000 m (Croughs et al, 2014). Previous studies assessing HRV and its links to HA have been partly undermined by the relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…There is some data to suggest that changes in HRV may be linked or even predictive of AMS though this still remains controversial (Lanfranchi et al, 2005;Chen et al, 2008;Koehle et al, 2010;Karinen et al, 2012;Wille et al, 2012;Song et al, 2013). This has important clinical implications as travel to HA has significantly increased in the last 10 years and AMS affects ≥35% of persons traveling to altitudes ≥3000 m (Croughs et al, 2014). Previous studies assessing HRV and its links to HA have been partly undermined by the relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…The search yielded a total of 532 articles. After reading the titles and abstracts, 48 articles were selected for full reading and 25 full-text articles met the inclusion criteria, 4,[11][12][13][14][15][16][17][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] corresponding to periods; for this reason, these two assessments were considered as two independent research studies. 26 The main characteristics for each separate study are presented in Table 1, and a complete overview of the articles is included in the supplementary material (Appendix 3, Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Of those with serious altitude illness, only 20% descended by the following day. 30 Similarly, a study of 991 travelers to Cusco, Peru (almost half of which were from the U.S.), showed that altitude illness was reported in 48% with severe symptoms in 17%. One in 5 travelers with altitude illness altered their travel plans due to illness.…”
Section: Injury Preventionmentioning
confidence: 96%